Efficacy of Jollab in the Treatment of Depression in Dyspeptic Patients: A Randomized Double-Blind Controlled Trial. (April 2015) - Pasalar, Mehdi; Choopani, Rasool; Mosaddegh, Mahmoud; Kamalinejad, Mohammad; Mohagheghzadeh, Abdolali; Fattahi, Mohammad Reza; Zarshenas, Mohammad M.; Jafari, Peyman; Lankarani, Kamran Bagheri
The current study aimed to evaluate the efficacy of jollab, a well-known beverage from traditional Persian medicine in the treatment of depression among patients suffering from functional dyspepsia. In a randomized, double-blind, placebo-controlled trial, a pair of 80 patients were enrolled in 2 parallel groups as Jollab and placebo. The Beck Depression Inventory–II questionnaire was used for the assessment. At all, 133 patients enrolling in the treatment and placebo groups ended the protocol. According to the outcomes, changes in scores between the 2 groups were statistically significant at the end of trial ( P ≤ .001). Taken as a whole, treatment group was significantly more effective than the placebo. Focusing on nutritional and pharmaceutical properties, jollab may be introduced not only as a medication for depression and allied ailment but also a pleasant daily drink.